Perencanaan Ekowisata Mangrove Desa Pasar Raya Menuju Desa Wisata Mangrove - Fitri, Rahmadhani; Siti Nurhayati; Arnita, Vina; Alfiyah, Sausan (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
Mangrove ecotourism has become one of the popular destinations in nature-based tourism. Pasar Raya Village, which is surrounded by beautiful mangrove forests, has taken the initiative to develop mangrove ecotourism and turn it into a "Mangrove Tourism Village." This study aims to design a comprehensive, sustainable, and attractive mangrove ecotourism planning in Pasar Raya Village. The study involved an in-depth analysis of the mangrove ecotourism potential, including the natural wealth, biodiversity, and environmental uniqueness of Pasar Raya Village. In addition, the involvement of local communities and stakeholders became an integral part of this planning. the construction of trails, jetties, and guided paths to allow visitors to explore the mangrove forest safely and comfortably. The outcome of this planning is the transformation of Pasar Raya Village into a sustainable mangrove ecotourism destination, which not only provides an exceptional experience for visitors but also empowers the local community and safeguards the important mangrove ecosystem. The success of this project depends on close collaboration between the government, community and private sector in a joint effort to maintain the natural beauty and biodiversity of Pasar Raya Village.